Electronic and structural properties of N → B-ladder boranes with high electron affinity. Issue 3 (12th December 2017) - Grandl, Markus; Sun, Yu; Pammer, Frank
Abstract : A series of electronically and structurally diverse N → B-ladder boranes has been prepared by hydroboration. Abstract : A series of new π-conjugated N → B-ladder boranes has been prepared in high yield by two-fold hydroboration of bifunctional quaterpyridine-, pyrimidine-, and 1, 5-naphthyridine-based precursors with 9 H -BBN and Piers' borane ((C6 F5 )2 BH). The structures of several ladder-boranes have been confirmed by X-ray crystallography, and their optical and electrochemical properties have been characterized, and complemented by DFT calculations. The electronic structure of the individual ladder boranes, as well as differences in the optical properties that originate from the chemical structure of the boryl-side-chains, are discussed. The results consistently show that, compared to the precursors, the optical gaps of the ladder boranes are significantly reduced, and the electron affinities are strongly increased to between −3.4 and −4.0 eV. Further investigations of chemically and electrochemically reduced species indicate that excess electrons in these kinds of systems are effectively delocalized throughout the conjugated systems.